The value of computing facilities in student residences - Richard Startup (Studies in Higher Education, 1988)
The aims of an experimental project were to examine the advantages gained by students from the provision of computer terminals in halls of residence and a student village; also to identify any managerial and operational problems which arose. There were problems of security and in accommodating the facilities but the primary gain was greater, more economical and more widespread use of the computer. A survey suggests that a majority of those coming to the university now have some prior experience of computing and predominantly positive attitudes towards it. Just under two-fifths of those in the residences had used the facilities and, significantly, one-fifth of these indicated that their pattern of work had altered to include more work in the evening, late at night and at weekends. There may exist the possibility for some students of a shift to a substantially non-campus based work schedule.